Adhesion molecule profiles of B-cell non-Hodgkin's lymphomas in the leukemic phase - Matos,D.M. (2006)
We evaluated the expression of 10 adhesion molecules on peripheral blood tumor cells of 17 patients with chronic lymphocytic leukemia, 17 with mantle-cell lymphoma, and 13 with nodal or splenic marginal B-cell lymphoma, all in the leukemic phase and before the beginning of any therapy. The diagnosis of B-cell non-Hodgkin's lymphomas was based on cytological, histological, immunophenotypic, and molecular biology methods. The mean fluorescence intensity of the adhesion molecules in tumor cells was measured by flow cytometry of CD19-positive cells and differed amongst the types of lymphomas. Comparison of chronic lymphocytic leukemia and mantle-cell lymphoma showed that the former presented a higher expression of CD11c and CD49c, and a lower expression of CD11b and CD49d adhesion molecules. Comparison of chronic lymphocytic leukemia and marginal B-cell lymphoma showed that the former presented a higher expression of CD49c and a lower expression of CD11a, CD11b, CD18, CD49d, CD29, and CD54. Finally, comparison of mantle-cell lymphoma and marginal B-cell lymphoma showed that marginal B-cell lymphoma had a higher expression of CD11a, CD11c, CD18, CD29, and CD54. Thus, the CD49c/CD49d pair consistently demonstrated a distinct pattern of expression in chronic lymphocytic leukemia compared with mantle-cell lymphoma and marginal B-cell lymphoma, which could be helpful for the differential diagnosis. Moreover, the distinct profiles of adhesion molecules in these diseases may be responsible for their different capacities to invade the blood stream.